Implementation of Project-Based Learning to Increase Student Engagement and Motivation in Learning Islamic Religious Education - St. Nuralimah; Muh Abdillah Maulana; Yang Peng (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: This study aims to increase students' learning motivation in Islamic Religious Education (PAI) through the application of Project-Based Learning (PJBL) model at SMP Negeri 2 Pallangga. Islamic Education has an important role in instilling moral, ethical, and religious values that are the basis of the life of the nation and state. However, the challenge faced in PAI learning is the low motivation of students to learn which has an impact on the understanding and application of religious values in everyday life. This study used the Classroom Action Research (PTK) method with a cyclical approach consisting of two cycles, referring to the classroom action research framework developed by Kemmis and McTaggart, involving 28 students. The research results from the first cycle showed that the majority of students were in the moderate category, with scores ranging from 59% to 73%. In the second cycle, all students managed to reach the “High” category, with scores ranging from 76% to 90%, reflecting the success of the teaching method applied. These findings suggest that PjBL is effective in increasing students' motivation by giving them control over the learning process and encouraging active participation in collaborative projects. This study concludes that PjBL can significantly improve students' engagement and achievement in Islamic Religious Education. Keywords: project-based learning, learning motivation, Islamic Religious Education.